1992
DOI: 10.1093/bja/68.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory and Auditory Evoked Responses Recorded Simultaneously: Differential Effects of Nitrous Oxide and Tsoflurane

Abstract: Auditory (AER) and somatosensory evoked responses (SSER) were recorded simultaneously in eight patients under anaesthesia before surgery. We studied the effects of equi-MAC end-expiratory concentrations of isoflurane (0.65-0.75%) and nitrous oxide (60-65%). The anaesthetics were changed at random in three consecutive 10-min periods so that each patient received both drugs. From the AER recorded from the vertex and inion, Pa and Nb latency and amplitude were measured. N13, P20 latency and N13 amplitude were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
24
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 0 publications
6
24
0
2
Order By: Relevance
“…The effects of medetomidine on SEPs do not appear to have been previously investigated. Isoflurane has consistently been shown to increase the latencies and decrease amplitudes of cortical SEPs (Sebel et al 1986, Thornton et al 1992. These changes are similar to those reported for other volatile anaesthetics (Thornton et al 1992).…”
supporting
confidence: 56%
See 2 more Smart Citations
“…The effects of medetomidine on SEPs do not appear to have been previously investigated. Isoflurane has consistently been shown to increase the latencies and decrease amplitudes of cortical SEPs (Sebel et al 1986, Thornton et al 1992. These changes are similar to those reported for other volatile anaesthetics (Thornton et al 1992).…”
supporting
confidence: 56%
“…An SEP is the electrical response of the nervous system produced by activation of a peripheral nerve, and consists of a series of peaks or waves, which are characterized by their polarity, latency and amplitude. SEPs can be useful in repeated longitudinal studies in the same animal, but anaesthetic agents can significantly affect their size and timing lAngeI & Gratton 1982, Sloan et al 1990, Thornton et al 1992). In order to carry out repeated periodic studies, it…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In eight patients Thornton et al identified a subsequent negative (N35) and positive deflection (P45) following N20-P25 complex during anesthesia. 12 They documented statistically different latency changes of N20 and P25 induced by isoflurane compared to nitrous oxide, while the latencies of two subsequent components were affected similarly by the two anesthetic agents. Isoflurane reduced amplitudes of P25-N35 and N35-P45 more profoundly, while the effect of nitrous oxide on the amplitude of the P15-N20 and the N20-P25 response was stronger.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, Thornton rt al. have used MLAEP in combination with somatosensory evoked responses to differentiate the hypnotic and analgesic effects of nitrous oxide [4]. We have embarked on a study recently and our preliminary findings do suggest that clonidine potentiates anaesthetic depth as indicated by MLAEP parameters during isoflurane anaesthesia, in patients undergoing gynaecological procedures.…”
Section: It Was Interesting To Read the Admonition Voiced By Drsmentioning
confidence: 99%